(untitled) (International Journal of Engineering and Computer Science, 2014)
AODV is a prominent routing protocol for MANET that uses hop count as a path selection metric. However, AODV has no means to convey traffic load on current route. In this paper we will survey protocols for load-balancing and energy-aware routing on MANET . This protocol is used for Internet gateway broadcasting route, and it evaluates route with node’s residual energy and transmission load. With this protocol node accessing Internet can find a shortest route and avoid low-power node and busy node. The routing strategy in this paper focuses on distributing the traffic on the routes consisting of nodes with comparatively longer life and have less traffic to pass through. Aggregate Interface Queue Length (AIQL), to deal with traffic issue. The weight of a route is decided by three factors: the aggregate interface queue length, the route energy and the hop count. The route with highest weight value is selected for further data transmission.